2002
DOI: 10.1016/s0022-2313(01)00243-5
|View full text |Cite
|
Sign up to set email alerts
|

Steady state and picosecond time-resolved photophysics of a benzimidazolocarbocyanine dye

Abstract: We report the steady-state and the excited state properties of 1, 3, 1 0 , 3 0 -tetraethyl-5, 6, 5 0 , 6 0 -tetrachlorobenzimidazolocarbocyanine iodide (TTBC) in various solvents. The magnitude of the Stokes shift and the average transition energy proves that the structure of the fluorescent state should be very similar to that of the ground-state structure. The fluorescence lifetimes and quantum yields indicate that non-radiative processes are collectively much more effective than the radiative processes. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Intersystem crossing, triplet formation and related deactivation channels of the first excited singlet state, i.e. the fluorescent state of cyanines are not very effective and have very low quantum yields [24][25][26][27][28][29][30][31][32]. Photoisomerisation and internal conversions leading to picosecond fluorescence lifetimes are considered as the main non-radiative deactivation pathways for cyanines [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Intersystem crossing, triplet formation and related deactivation channels of the first excited singlet state, i.e. the fluorescent state of cyanines are not very effective and have very low quantum yields [24][25][26][27][28][29][30][31][32]. Photoisomerisation and internal conversions leading to picosecond fluorescence lifetimes are considered as the main non-radiative deactivation pathways for cyanines [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with the reported solvatochromism observed for TTBC monomer in various solvents. 30 It is confirmed that TTBC molecules were molecularly dispersed in PVA solution, and the spinning solution was initially free of aggregates.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…The simulated absorption and fluorescence spectrum of TTBC will be compared with the experimental spectra reported by Özçelik [18]. This versatile organic dye is an important biological molecular probe; it is envisioned that the knowledge gained from our work here may benefit the use and development of the optical and spectroscopic properties of this and similar dyes.…”
Section: Introductionmentioning
confidence: 90%
“…An experimental fluorescence maximum appears at 528 nm with a shoulder located at 560 nm in methanol; however, the bathochromic shift with solvent polarity was not observed. The dual emission was suggested experimentally only in glycerol where a double exponential decay was detected [18]. However there is no experimental evidence of a charge transfer state for that dye.…”
Section: Homo-1 Lumo+1mentioning
confidence: 99%
See 1 more Smart Citation